ANALYSIS OF THE PREVALENCE OF OBESITY AND PRACTICE OF PHYSICAL EXERCISES IN THE PRIVATE AND PUBLIC EDUCATION NETWORK (Fiep Bulletin - online, 2019)
The occurrence of childhood obesity reaches worrying rates. The theme has acquired important importance, mainlydue to the impact that can cause in the life of children, bringing physical, social, economic and psychological consequences. Toverify the prevalence of obesity and the practice of physical exercises among students from 7 to 10 years of age enrolled inelementary school I. Descriptive exploratory study of quantitative approach. Held in the municipality of Itaporanga-PB, and hadtwo study institutions, one from the private network and another from the public network. The sample consisted of 134 students ofboth sexes, where 64 students are from the public school and 70 students from the private school. To collect data, twoquestionnaires were used to verify the eating habits in the school and their level of physical activity. The data collected wastabulated through the Microsoft Office Excel 2007 program and processed through the SPSS statistical program. Regardingdietary habits, it was possible to verify that the private school has a greater supply of products rich in carbohydrates andindustrialized when compared to public school and the adhesion to physical activities was practically nonexistent in both schools.Therefore, the results of the study show the need to implement and / or implement strategies that envisage an adequate diet, suchas the stimulation of physical activity among children, so that a future quality of life and reduction of the obesity index.
Keywords: Obesity. Physical exercises. Child